Career impact of the national interprofessional fellowship in patient safety: an alumni evaluation - Bradley V Watts; Kathleen Carluzzo; Blake F Webb; Kelley Arredondo (BMJ Open Quality)
Background There has been a proliferation of health professions training programmes focused on quality and patient safety, but little information regarding the outcomes of these programmes. The purpose of this study was to examine the impact of an interprofessional quality and patient safety curriculum on career outcomes of interprofessional healthcare learners for the Veterans Affairs Patient Safety Fellowship.Method We conducted a survey-based assessment of 117 alumni of the Interprofessional Fellowship in Patient Safety assessing their satisfaction with the training program and career impacts.Results 84 of 117 alumni were located and participated in the assessment. Fellows entered the training programme from a wide range of educational experiences, but most were in their early career at entry. Satisfaction with the training programme was high, with 42% (n=35) of alumni reporting being extremely satisfied with their fellowship experience. Programme alumni reported being either extremely or very knowledgeable about quality and patient safety (77%, n=65). Fellows reported considerable engagement with the academic field of patient safety and quality, with 63% (n=53) having published at least one manuscript about the topic and 75% (n=63) reporting a role teaching patient safety and quality improvement. Fellows’ employments post training were quite varied, although positions focused on health profession education were most common.Conclusions The Interprofessional Fellowship in Patient Safety is an early successful example of an interprofessional training programme that resulted in satisfied alumni who reported good knowledge and abilities in the topic of patient safety. Career pathways were varied, but a focus on health professions education post fellowship was prominent.